The Epidemiological surveillance of Human Papillomavirus (HPV) genotypes in oral and genital tracts and the impact of HPV vaccination on male university students from Rio de Janeiro state, Brazil - Silva, Kátia Cristina da; Rocha, Willker Menezes da; Pereira, Milena Siqueira; Andrade, Hugo Boechat; Gouvea, Tegnus Depes de; Kury, Charbell Miguel Haddad; Passos, Mauro Romero Leal; Cavalcanti, Silvia Maria Baeta (Brazilian Journal of Sexually Transmitted Diseases, 2023)
Introduction: Human Papillomavirus (HPV) infections are of significant concern in men, given its potential impact on their health and the risk of transmission to partners. Understanding and addressing this infection in men is crucial to evaluate the effectiveness of vaccination in reducing HPV-related diseases. Objective: To assess the impact of HPV vaccination, potential genotype shifts, and adverse effects, through a prospective study conducted with male university students. Methods: The study involved 286 volunteers who were examined at Sexually Transmitted Disease Clinics at the Universidade Federal Fluminense in Niterói, Rio de Janeiro, Brazil. The HPV prevalence was evaluated using generic PCR, genotyped by DNA microarray and monitored adverse effects. Results: The findings of this study revealed the absence of moderate or severe adverse effects. Genetic shifts were observed, including the disappearance of oncogenic HPV types 16 and 18. Surprisingly, even after completing the full vaccine regimen, students still harbored HPV11 in the oral tract. Furthermore, persistent HPV 6 and 11 infections were identified in three students, who had pre-existing infections prior to vaccination, at the follow-up visit. Multivariate analysis uncovered independent associations, notably an increased risk of HPV infection in the oral tract among men who have sex with men. HPV prevalence rates remained low both before and after the vaccination scheme (T0: 14.7%, T1: 8.7%). Even after the full vaccination scheme, the prevalence remained similar at T2 (14.6%), with no statistically significant differences recorded. HPV11 emerged as the most prevalent type throughout the study, followed by HPV6. Vaccine genotypes were detected in a significant proportion of samples at T0 (85.4%), T1 (89.5%), and T2 (100%). Conclusion: Overall, this study suggests that vaccination may represent a promising approach to reducing HPV-related health risks. These findings shed light on the potential benefits and challenges of HPV vaccination, emphasizing the need for continued monitoring and vaccination efforts.